The Hidden Life of Polish Prisons - Moczydłowski, Paweł (Indiana University Press, 1992)
The first behind-the-walls look at the "hidden life" of Polish prisons, this book penetrates the inmates' façade of silence and deception toward outsiders and presents a vivit portrait of the prison's secret social organization.